Cheilitis granulomatosa associated with lupus erythematosus discoid and treated with methotrexate: report of a case - Gianluca Nazzaro; Simona Muratori; Carlo Giovanni Carrera; Antonella Coggi; Raffaele Gianotti (Sociedade Brasileira de Dermatologia, 2015)
Abstract We present the rare case of a 47-year-old patient, suffering from cheilitis granulomatosa and lupus erythematosus discoid: this association is really exceptional because only once reported in English literature. In addition, the treatment of cheilitis granulomatosa is a challenge for the dermatologist: the gold standard, represented by steroids, is in fact designed as a short-time option. Our report confi rms the good efficacy of methotrexate as a steroid-sparing agent.